An Agent-Based Model for Addressing the Impact of a Disaster on Access to Primary Care Services. (14th April 2016) - Guclu, Hasan; Kumar, Supriya; Galloway, David; Krauland, Mary; Sood, Rishi; Bocour, Angelica; Hershey, Tina Batra; van Nostrand, Elizabeth; Potter, Margaret
Abstract: Objective: Hurricane Sandy in the Rockaways, Queens, forced residents to evacuate and primary care providers to close or curtail operations. A large deficit in primary care access was apparent in the immediate aftermath of the storm. Our objective was to build a computational model to aid responders in planning to situate primary care services in a disaster-affected area. Methods: Using an agent-based modeling platform, HAZEL, we simulated the Rockaways population, its evacuation behavior, and primary care providers' availability in the aftermath of Hurricane Sandy. Data sources for this model included post-storm and community health surveys from New York City, a survey of the Rockaways primary care providers, and research literature. The model then tested geospatially specific interventions to address storm-related access deficits. Results: The model revealed that areas of high primary care access deficit were concentrated in the eastern part of the Rockaways. Placing mobile health clinics in the most populous census tracts reduced the access deficit significantly, whereas increasing providers' capacity by 50% reduced the deficit to a lesser degree. Conclusions: An agent-based model may be a useful tool to have in place so that policy makers can conduct scenario-based analyses to plan interventions optimally in the event of a disaster. ( Disaster Med Public Health Preparedness . 2016;10:386–393)